Food, energy, and water nexus research in Guatemala – A systematic literature review. Issue 124 (October 2021) - Kondash, A.J.; Herrera, Isabel; Castellanos, Edwin; Baker, Justin; Leiva, Benjamín; Van Houtven, George; Fuentes, Gabriela; Alfaro, Gabriela; Henry, Candise; Wade, Christopher; Hoponick Redmon, Jennifer
Highlights: Food, energy, and water systems are mainly studied independently in Guatemala. Only 46 % of studies examined 2 or more integrated food, energy, or water systems. There are multiple data gaps and no integrated approach to address FEW development. Only 42 % of studies related to the nexus in Guatemala created original data. Water access/quality, crop irrigation, and renewable energy are key nexus issues. Abstract: The interconnectedness of food, energy, and water systems – commonly referred as the FEW nexus - calls for the integrated study of these systems to improve resiliency of these natural resources and adapt to our changing world. In this article, we explore the state of FEW nexus research in Guatemala to highlight progress while also pointing out future research needs. A systematic literature review was conducted to identify peer-reviewed articles and grey literature published on this topic from January 2000 to May 2020. Articles were reviewed and classified to identify the Guatemalan study location, type, topic, and data sources. Only a limited number of studies explored the interconnectedness of FEW systems; 26% of articles (36 out of 138) focused on two aspects of the FEW nexus, while 20% (27 out of 138) focused on all three aspects. Water issues were the most commonly studied, with drinking water, hydroelectricity, and wastewater management being frequently discussed. We also identified a low rate of primary data generation, with only 42% articles (58 of 138) generating new data, and greater emphasis of nexus research in the grey literature. The Guatemalan FEW connections revolve primarily around three separate yet related spheres: clean water and sanitation, climate change and renewable energy, and urbanization and modernization. Further expanding initiatives that simultaneously address these three spheres would yield improved understanding of the interconnected roles that food, energy, and water play in improving the resiliency of natural resources and reducing multidimensional poverty in Guatemala.